CASH FLOW DESIGN STUDY IN ROAD WORKS-ROAD WIDENING PROJECT ON KURNIA STREET NORTH LANDASAN ULIN BANJARBARU - Ahmad Anshori; Candra Yuliana (Universitas Lambung Mangkurat, 2021)
The effect of planning on construction projects will have an impact on income within the project itself. Usually, the realization of work plans in the field often experiences delays in the process, because the number of revenue was determined by the method of payment stipulated in the construction contract. Payment system aspects affect the working capital that needs to be provided by the contractor. Therefore, the role of planning the flow of cash flow is very substantial in the implementation of the project. The purpose of this study is to get a cash flow plan with a Monthly Payment system and Progress Payment system based on the project schedule of the Road Works-Road Widening On Kurnia Street North Landasan Ulin Banjarbaru. The method used to analyze the data is project scheduling by making the description and sequence each activity, determining the duration for each project work, and making a project network diagram using the PDM Method ( Precedence Diagram Method ). Then make a cash flow analysis with monthly payment system and progress payment with three payments, at cumulative progress 30.04%, 70.28%, and 100% on the conditions of EST ( Earliest Start Time ) and LST ( Latest Start Time ) schedule. The results of the data analysis show that the payment system that provides maximum benefits is the Monthly Payment system using a 20% down payment on the EST ( Earliest Start Time ) and LST ( Latest Start Time ) schedule conditions with a total loan of Rp. 653,000,000, the contractor gets a profit of Rp. 490,990,222 with a percentage of profits of 8,892%.